The Relationship between Spending on Education and the unemployment index in the framework of causality and co- integration in the Kingdom of Saudi Arabia during the period (2000- 2020) - Alrashidi, Sarah Mohmmed; Alshaeya, Ali Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the extent of the existence of a causal relationship between spending on education in Saudi Arabia and the unemployment index during the period (2000- 2020), The research used the descriptive method And the co- integration test using the Engel and Granger methodology in the EVIEWS program to determine the causal relationship between education spending and the unemployment index, the study concluded that the relative deviation of the unemployment index during the period (2000- 2020) is small, which indicates the limited impact and relationship, and that the level of decline is slight, The average education budget in the period from 2000 to 2020 amounted to (130.4826000) million Saudi riyals, By conducting the Engel- Granger test, the unemployment index doesn't account for the rate of expenditure on education, Because P = 0.4256 is greater than 0.05, so there is no causal relationship between spending on education and unemployment, hence the causality test says that spending on education contributes to reducing unemployment rates. The study recommends expanding the effort to search for other factors affecting the unemployment index to achieve more efficiency.
Keywords: causation; unemployment; spending on education; renaissance; social justice